Attitudinal profile of the young EFL beginner: findings of the Croatian project - Mihaljević Djigunović, Jelena (Array, 1999)
The article looks into some of the affective characteristics of young ELF learners. The author discusses the development of the initial attitudes of 7-year-old beginners, focusing particularly on whether young beginners viewed their foreign language classes differently afte three years of learning, whether their attitudes towards native speakers of the language they were learning had changed, as well as their self-rating of foreign language skills. The author concludes that the affective variables of the young beginners showed positive trends and desirable characteristics that may be viewed as conducive to successful language learning.